Ecology and Inclusive Education - Sharma, Indu (JOURNAL OF INDIAN EDUCATION, 2022)
The concept of ‘ecology’ has been thoroughly researched in the past, but the possibility of its applicability in inclusive education is something that is yet to be explored in depth. The ecological lens has been significant in the education sector to understand and assess the learning behaviour and outcomes of students in a classroom environment. Here is an attempt to comprehend the diverse multiple perspectives of ecology in the diaspora of inclusive education. Through this paper, an understanding has been developed that this ecological lens has not been utilised in varied contexts (like the relevance of ecology in developmental research) of the teaching-learning process for Children With Special Needs (CWSN). Keeping in mind the nascent awareness and acceptance of inclusion in the field of education, the paper explores the significance of ecological orientation in educational practices.